2011
DOI: 10.1021/jo201358e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mutual Azo Prodrugs of Anti-inflammatory Agents and Peptides Facilitated by α-Aminoisobutyric Acid

Abstract: Reported is the synthesis of azo mutual prodrugs of the nonsteroidal anti-inflammatory agents (NSAIDs) 4-aminophenylacetic acid (4-APAA) or 5-aminosalicylic acid (5-ASA) with peptides, including an antibiotic peptide temporin analogue modified at the amino terminal by an α-aminoisobutyric acid (Aib) residue. These prodrugs are designed for colonic delivery of two agents to treat infection and inflammation by the bacterial pathogen Clostridium difficile .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The use of azo‐linked compounds for specific drug delivery to the gut remains an area of great interest. As well as anti‐inflammatory compounds, azo chemistry has been used to target a range of other drugs and they include antibiotics (Kennedy et al , ; Deka et al , ) and anticancer drugs (Sharma et al , ; Plyduang et al , ). Development continues on new azo‐bonded carriers for drugs (Ruiz et al , ; Kim et al , ) as well as linking pairs of drugs together (Ruiz et al , ).…”
Section: Azo Drugsmentioning
confidence: 99%
“…The use of azo‐linked compounds for specific drug delivery to the gut remains an area of great interest. As well as anti‐inflammatory compounds, azo chemistry has been used to target a range of other drugs and they include antibiotics (Kennedy et al , ; Deka et al , ) and anticancer drugs (Sharma et al , ; Plyduang et al , ). Development continues on new azo‐bonded carriers for drugs (Ruiz et al , ; Kim et al , ) as well as linking pairs of drugs together (Ruiz et al , ).…”
Section: Azo Drugsmentioning
confidence: 99%
“…In 2011, Kennedy et al [268] reported the synthesis of azo mutual prodrugs containing 5-aminophenylacetic acid or 5-aminosalicylic acid (5-ASA) with antimicrobial peptides. The prodrugs were designed to deliver nonsteroidal anti-inflammatory agents (NSAIDs) with an antimicrobial agent to treat both the infection and symptoms caused by C. difficile .…”
Section: Newer Agents For CDImentioning
confidence: 99%
“…The aim was to protect the ammonium terminal of the antimicrobial peptide by an azo bond with an anilinic anti-inflammatory agent so that both components are maintained in an inactive state before reaching its site of action in the colon. This would potentially increase therapeutic outcomes, as it would avoid the ulceration side effects of the NSAID and reduce the disruption of the native microbiota by the antimicrobial peptide while it passes through the upper GI tract [268]. An analog of temporin A, L512TA was used as the antimicrobial peptide portion of the prodrug.…”
Section: Newer Agents For CDImentioning
confidence: 99%
“…The various methods reported, however, had their own drawbacks: some reactions and/or the by‐products contain mercury, requiring special safety precautions and disposal methods; some reactions have to be performed in an aqueous environment, which would limit the application for moisture‐sensitive substances. Recently, Kennedy et al reported that α‐hydrazo acid can be converted to the α‐azo acid by exposure to air.…”
Section: Resultsmentioning
confidence: 99%